Chalcogenide glass-on-graphene photonics. Issue 12 (December 2017) - Lin, Hongtao; Song, Yi; Huang, Yizhong; Kita, Derek; Deckoff-Jones, Skylar; Wang, Kaiqi; Li, Lan; Li, Junying; Zheng, Hanyu; Luo, Zhengqian; Wang, Haozhe; Novak, Spencer; et al.
Abstract Two-dimensional (2D) materials are of tremendous interest to integrated photonics, given their singular optical characteristics spanning light emission, modulation, saturable absorption and nonlinear optics. To harness their optical properties, these atomically thin materials are usually attached onto prefabricated devices via a transfer process. Here, we present a new route for 2D material integration with planar photonics. Central to this approach is the use of chalcogenide glass, a multifunctional material that can be directly deposited and patterned on a wide variety of 2D materials and can simultaneously function as the light-guiding medium, a gate dielectric and a passivation layer for 2D materials. Besides achieving improved fabrication yield and throughput compared with the traditional transfer process, our technique also enables unconventional multilayer device geometries optimally designed for enhancing light–matter interactions in the 2D layers. Capitalizing on this facile integration method, we demonstrate a series of high-performance glass-on-graphene devices including ultra-broadband on-chip polarizers, energy-efficient thermo-optic switches, as well as graphene-based mid-infrared waveguide-integrated photodetectors and modulators. Exploiting the peculiar properties of graphene, a series of high-performance glass-on-graphene devices, such as polarizers, thermo-optic switches and mid-infrared waveguide-integrated photodetectors and modulators are realized.